A novel inhibitory mechanism of MRTF-A/B on the ICAM-1 gene expression in vascular endothelial cells - Hayashi, Ken'Ichiro; Murai, Toshiyuki; Oikawa, Hiroki; Masuda, Tomoyuki; Kimura, Kazuhiro; Muehlich, Susanne; Prywes, Ron; Morita, Tsuyoshi (Scientific Reports, 2015)
The roles of myocardin-related transcription factor A (MRTF-A) and MRTF-B in vascular endothelial cells are not completely understood. Here, we found a novel regulatory mechanism for MRTF-A/B function. MRTF-A/B tend to accumulate in the nucleus in arterial endothelial cells in vivo and human aortic endothelial cells (HAoECs) in vitro. In HAoECs, nuclear localization of MRTF-A/B was not significantly affected by Y27632 or latrunculin B, primarily due to the reduced binding of MRTF-A/B to G-actin and in part, to the low level of MRTF-A phosphorylation by ERK. MRTF-A/B downregulation by serum depletion or transfection of siRNA against MRTF-A and/or MRTF-B induced ICAM-1 expression in HAoECs. It is known that nuclear import of nuclear factor κ B (NFκ B) plays a key role in ICAM-1 gene transcription. However, nuclear accumulation of NFκ B p65 was not observed in MRTF-A/B-depleted HAoECs. Our present findings suggest that MRTF-A/B inhibit ICAM-1 mRNA expression by forming a complex with NFκ B p65 in the nucleus. Conversely, downregulation of MRTF-A/B alleviates this negative regulation without further translocation of NF κB p65 into the nucleus. These results reveal the novel roles of MRTF-A/B in the homeostasis of vascular endothelium.
CRIS-Team Scopus Importer:2024-07-10